Assessment of the Vulnerability of the Expediture Accounting in the National Statistical System in View of the Internal Audit: Array - Iuga Dîndăreanu, Viorica (Acta Universitatis Danubius. Œconomica, 2021)
By means of the expenditure accounting specific for the national statistical sector can be quantified the efforts made towards the implementation of strategic objectives, general and specific objectives related to the activities carried out by relevant public entities that collect, centralize, aggregate, analyze and process economic, financial, social information and so on. The assessment made by the internal audit on the accounting of expenditure specific to the national statistical sector adds value to this complex activity, which is particularly important for a public entity management. Following the identification and assessment of the accounting vulnerability in the national statistical system in terms of internal audit, the hypothesis is validated according to which the internal audit activity contributes to the identification of strengths and weaknesses of the accounting of this system.